Analysis of Natural Responses and Hydrochemical Data by Statistical Approaches as a Tool to Understanding the Hydrogeological Functioning of a Highly Karstified Evaporitic System in South Spain - Gil-Márquez, José Manuel; Mudarra-Martínez, Matías; Andreo-Navarro, Bartolomé (My University, 2016)
At southern Cordoba Province (Spain), an evaporitic karst plateau drained by brine springs is located. A periodic monitoring of discharge rate, EC, water temperature, and pH was performed in one of them (Lower Anzur spring) and water samples were collected for chemical analysis. Physicochemical data were used to perform a principal component analysis (PCA) to characterize the functioning of the system. Temporal evolution of the controlled parameters reveals a markedly karst behavior. PCA has defined two principal factors, one related to salinity and other linked to infiltration processes (NO3−, Ca2+). The slight thermal anomaly and the high mineralization registered indicate the existence of ascending regional groundwater flows of long residence time, which would converge into the spring, mixed with recently infiltrated water that circulated through a conduit network formed in the evaporite rocks
Keywords: Karst; Hidrología kárstica; Hidrogeología; Evaporitas